Organizational Conflict 2018
DOI: 10.5772/intechopen.71579
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts as Springboard for Metallica’s Success

Abstract: The purpose of this chapter is to understand how Metallica has utilized conflicts in creating changes in the music industry and growing as the biggest heavy metal band of the world and sustained in this position for 25 years. The study was conducted as a qualitative and longitudinal case study. The study confirmed that conflicts have been a crucial factor in Metallica's success. The interpersonal conflicts and the conflicts between the band founders have been pivotal. The duo has competed and collaborated agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Metallica gained its strength from negative emotions: fear of losing control and hatred against authorities. This is in line with Jalonen et al (2016) and Salmela (2017), who mention that properly utilized negative emotions can be turned into a competitive advantage. In conflict situations, fear increases the intention to avoid conflict or accommodate to it, and decreases intention to compete.…”
Section: Angry and Innovative Underdog As Conflict Stimulatorsupporting
confidence: 88%
See 1 more Smart Citation
“…Metallica gained its strength from negative emotions: fear of losing control and hatred against authorities. This is in line with Jalonen et al (2016) and Salmela (2017), who mention that properly utilized negative emotions can be turned into a competitive advantage. In conflict situations, fear increases the intention to avoid conflict or accommodate to it, and decreases intention to compete.…”
Section: Angry and Innovative Underdog As Conflict Stimulatorsupporting
confidence: 88%
“…Metallica did not follow the rules of the music industry, which caused constant conflicts with partners (Brannigan & Winwood, 2013; Eglinton, 2010; McIver, 2009). Salmela (2017) has studied Metallica's internal conflicts and showed that interpersonal conflicts between the band founders were a crucial factor in Metallica's success. He suggests that it would be necessary to study Metallica's conflicts also with its partners.…”
Section: Methodsmentioning
confidence: 99%